IMPLEMENTATION OF RELIABILITY CENTERED MAINTENANCE (RCM) IN PERTAMINA HULU ENERGY SUBHOLDING UPSTREAM (PHE SHU) THROUGH PERTAMINA RELIABILITY DATA (PAREDA) DATABASE & APPLICATION DEVELOPMENT - Fikri, Khairil; Darmadi , Djarot B.; Nuggraha , Deddy; Tieu , Anh Kiet; Norrish , John (International Journal of Mechanical Engineering Technologies and Applications, 2023)
As part of the integrated efforts that need to be made to achieve the target of becoming a world-class energy company, PHE SHU needs to carry out a series of strategic initiative programs related to the implementation of RCM which need to be carried out in several field including all Regions, Zones, Work Areas and Assets. In the context of implementing RCM at PHE SHU, management has carried out a series of massive and simultaneous activities during 2022-2023 period, both debriefing several workshops & socialization of RCM understanding, issuing task forces and director's orders, conducting site visits & field implementation pilot projects in the onshore area (GTC SKG Subang Field) as well as offshore area (GTG X-Ray Jatibarang Field), performing sharing sessions/focus group discussion, review maturity level assessment, initiate various continuous improvement and its replication to other fields, as well as database development and created Pertamina Reliability Data (PAREDA) applications.